The efficacy of flubendazole against Trichinella spiralis in swine - Marinculić A.; Fajdiga M.; Duraković E. (Parasite, 2001)
A trial was undertaken to assess the efficacy of flubendazole against experimentally induced trichinellosis in pigs when given mixed with food at different dose rates. At the start of the experiment, 48 pigs were infected with approximately 35,000 larvae of Trichinella spiralis, afterwhat the animals were distributed in six groups. The first three groups were used to test the activity of the drug against adult stages. Other three groups served to define the efficacy against muscle larvae. The dose rate of flubendazole varied according to the purpose of the experiment (from 8 mg/kg up to 62 mg/kg). At the end of the trial, the pigs were necropsied and the number of adults and larvae in predilection muscles were determined. At a dose rate of 8 mg/kg flubendazole supplied with food during eight days was 100 % effective against adults. At a dose rate of 31 mg/kg flubendazole administered for 14 days was 72.35 % effective. Treatment with higher dosages of flubendazole (62 mg/kg) resulted in increased efficacy (87.77 %) against the parasites. The biological assay performed with larvae from the muscle samples originating from the pigs treated with 62 mg/kg showed that at least half of the larvae were not infective.